Modular Ontologies - Kutz, Oliver (IOS Press, 2014)
Modularity, in its different shapes and forms, remains one of the central research topics in ontology engineering, still catching up with 40 years of related research in software engineering. The workshops on Modular Ontologies (WoMO) bring together researchers from different disciplines who study the problem of modularity in ontologies at a fundamental level, develop design tools for distributed ontology engineering and apply modularity in different use cases and application scenarios.The contributions in this volume are of interest to researchers, students and practitioners interested in Semantic Web ontologies, their languages and tools and specifically, to research groups working on ontology modularization and integration problems and corresponding tools. They should also be of interest to the broader communities of knowledge representation and reasoning, information integration, description logics and ontology languages, distributed systems and to practitioners from Semantic Web and other emerging application domains for ontologies such as life sciences, robotics, e-business and ambient intelligence.